Pengembangan Media Pembelajaran Video Tutorial Penggunaan Wheel Balancer - Viki Ari Rosyadi; Ibnu Siswanto (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2026)
Abstract This study aimed to develop and evaluate the feasibility of a video tutorial learning medium for operating the Krisbow Pro EPBC24 wheel balancer in the Steering, Brake, and Suspension course at the Department of Automotive Engineering Education, Universitas Negeri Yogyakarta. The study was motivated by students' difficulty in understanding the operation of a new wheel balancer and the limited availability of visual learning guides that match actual workshop conditions. This research used a Research and Development approach with the 4D model, consisting of define, design, develop, and disseminate stages. The product was developed through needs analysis, preparation of learning content, script and storyboard design, video recording in the chassis workshop, video editing, expert validation, revision, and limited dissemination through digital platforms. Product feasibility was assessed by one material expert, one media expert, and 54 students who had completed the Steering, Brake, and Suspension course. Data were collected using four-point Likert scale questionnaires and analyzed descriptively using feasibility percentage scores. The material expert validation obtained a score of 63 out of 68, or 92.65%, while the media expert validation obtained a score of 102 out of 108, or 94.44%. Student responses reached a total score of 3,797 out of 4,320, or 87.89%. All results were categorized as highly feasible. These findings indicate that the wheel balancer video tutorial is feasible as a supplementary medium for workshop practice because it provides clear work procedures, visual guidance, and flexible access for independent learning. Abstrak Penelitian ini bertujuan mengembangkan dan menilai kelayakan media pembelajaran video tutorial penggunaan wheel balancer Krisbow Pro EPBC24 pada mata kuliah Kemudi, Rem, dan Suspensi di Departemen Pendidikan Teknik Otomotif Universitas Negeri Yogyakarta. Penelitian dilatarbelakangi oleh kesulitan mahasiswa dalam memahami prosedur penggunaan alat wheel balancer yang relatif baru dan belum tersedianya panduan visual yang sesuai dengan kondisi bengkel praktik. Penelitian ini menggunakan metode Research and Development dengan model 4D yang meliputi tahap define, design, develop, dan disseminate. Produk dikembangkan melalui analisis kebutuhan, penyusunan materi, pembuatan naskah dan storyboard, pengambilan gambar di bengkel chasis, penyuntingan video, validasi ahli, revisi produk, serta penyebaran terbatas melalui media digital. Kelayakan produk dinilai oleh satu ahli materi, satu ahli media, dan 54 mahasiswa yang telah menempuh mata kuliah Kemudi, Rem, dan Suspensi. Data dikumpulkan menggunakan angket skala Likert empat tingkat dan dianalisis secara deskriptif dalam bentuk persentase kelayakan. Hasil validasi ahli materi memperoleh skor 63 dari 68 atau 92,65%, sedangkan validasi ahli media memperoleh skor 102 dari 108 atau 94,44%. Respons mahasiswa memperoleh skor 3.797 dari 4.320 atau 87,89%. Seluruh hasil penilaian berada pada kategori sangat layak. Temuan tersebut menunjukkan bahwa video tutorial penggunaan wheel balancer layak digunakan sebagai media pendukung praktik karena menyajikan prosedur kerja yang jelas, panduan visual yang mudah dipahami, dan akses fleksibel untuk pembelajaran mandiri.